MODELING OF BONE INJURIES IN ANIMAL EXPERIMENTS - A. Sh. Ananeva; L. M. Baraeva; I. M. Bykov; Yu. V. Verevkina; A. N. Kurzanov (Инновационная медицина Кубани, 2021)
In this review, we discuss the advantages and disadvantages of the existing bone defect animal models and tissue engineering techniques applied in studying novel bone defect regenerative approaches. The paper suggests the requirements for an optimal animal model, as well as analyzes in vivo bone injury models widely used in testing. The authors briefly review the methods of experimentally produced lesions of long bones, calvarial bones, mandibular bones in different animals. This review also describes the standardization techniques allowing one to evaluate the process of osteogenesis and bone-implant interactions. That will help researchers thoroughly plan and conduct experiments according to the bioethical principles.